2021
DOI: 10.3329/bjms.v20i3.52803
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Cognitive Function Assessment during Pregnancy: An Event-Related Potential and Neuropsychological Study

Abstract: Objectives: We investigated the auditory cognitive and behavioral functions during 2nd and 3rd trimesters of pregnancy using event-related potentials (ERPs) and different neuropsychology tests, respectively. Methods: The ERPs were studied by using a 128-sensor net, and PAS/COWA, WCST, ZCT, RAVLTIM/RAVLTDR/RAVLTTS, and BDI were tested for neuropsychology assessment. Total 39 subjects were recruited for control group (G1, n=15, non-pregnant), 2nd trimester group (G2, n=12, 13-26 weeks gestation), and 3rd t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…P300 represents attentional resource allocation during memory updating [ 75 , 76 ], which also reflects the activity of the left temporoparietal brain region and the left prefrontal area [ 77 , 78 , 79 , 80 ]. Begum and Reza (2021) used a 128-electrode sensor net to study auditory cognitive function in pregnant women, and found that the pregnancy group produced the highest amplitude at the Fp1 electrode in terms of the P300 component [ 81 ]. The P300 component measured in the Fp1 position indicates that the attribution of the individual is similar to the changes in the neural processes caused by the cognition of garbage classification.…”
Section: Discussionmentioning
confidence: 99%
“…P300 represents attentional resource allocation during memory updating [ 75 , 76 ], which also reflects the activity of the left temporoparietal brain region and the left prefrontal area [ 77 , 78 , 79 , 80 ]. Begum and Reza (2021) used a 128-electrode sensor net to study auditory cognitive function in pregnant women, and found that the pregnancy group produced the highest amplitude at the Fp1 electrode in terms of the P300 component [ 81 ]. The P300 component measured in the Fp1 position indicates that the attribution of the individual is similar to the changes in the neural processes caused by the cognition of garbage classification.…”
Section: Discussionmentioning
confidence: 99%
“…The event-related potential (ERP) is used to record a brain signal as it is a non-invasive and risk-free method during auditory and visual stimulus (Key et al, 2005). According to Begum & Reza (2021), ERP responses are divided into 2; early wave (first 100 ms after stimulation) and late wave (after 100 ms after stimulus) can be recorded during ERP study. To measure consumers' decision-making, P300 is the main component of brainwaves, a basis in decision-making (Luck, 2005), and the catalyst for the brain to process incoming information.…”
Section: P300 and Decision Makingmentioning
confidence: 99%
“…Notably, some studies indicate a pronounced memory decline in the second trimester, 13 while others propose that pregnant women exhibit poorer memory performance throughout all three trimesters 18,28 . Additional research indicates memory impairments as particularly evident during the third trimester 10,20,34,35 . In a recent meta‐analysis 10 focusing on pregnancy and cognitive function, the authors concluded that cognitive function in pregnant women is inferior compared to the control group, especially during the third trimester.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we compared the performance of pregnant (third trimester) and nonpregnant women across several memory and inhibitory control tests, as well as brain ERPs and salivary cortisol levels. Regarding the tests’ performance, based on our own and others’ previous studies, 9,15,24,34,42 we expect the groups to differ in RTs, with pregnant women demonstrating slower RTs compared to nonpregnant ones. Additionally, we expected pregnant women to demonstrate higher inhibitory control abilities, reflected in their enhanced capability to inhibit responses on stop‐signal trials, along with significant group differences in brain activity patterns (e.g., P300 amplitude) and in levels of salivary cortisol 42 …”
Section: Introductionmentioning
confidence: 99%